The Persuasive Strategies Found in Beauty Products Slogans on Instagram - Losi, Rizky Vita; Meliala, Moses Hirja; Izar, Julisah (Best Journal of Administration and Management, 2023)
Language is essential to be used to advertise products. This study purposed to find the persuasive strategies used in beauty products slogans on Instagram. This study used descriptive qualitative as the research design and textual analysis was used to analyze the data. There were 50 data which were taken from the slogans of Wardah product advertisements. Based on the data analysis, it was found that there were ethos (16 data), pathos (11 data) and logos (11 data). The findings on the use of ethos became the most used strategy in the slogans. The advertisement used pathos to persuade the consumers’ feeling or emotion to be attractive to buy the products.